Bone structure assessed with pQCT in prepubertal males with delayed puberty or congenital hypogonadotropic hypogonadism. (28th March 2021) - Varimo, Tero; Miettinen, Päivi J.; Laine, Tiina; Salonen, Pia; Tenhola, Sirpa; Voutilainen, Raimo; Huopio, Hanna; Hero, Matti; Raivio, Taneli
Abstract: Objective: Congenital hypogonadotropic hypogonadism (CHH) is associated with impaired bone mineral density in adulthood, whereas the estimates on bone structure in adolescents with CHH has not been previously evaluated. This study describes bone structure in CHH patients and compares it to that in boys with constitutional delay of growth and puberty (CDGP). Design: A cross‐sectional study. Methods: Peripheral quantitative computed tomography (pQCT) of non‐dominant arm and left leg were performed. Volumetric bone mineral density (BMD), bone mineral content, and area in trabecular and cortical bone compartments were evaluated, and bone age‐adjusted Z‐scores for the bone parameters were determined. Results: The participants with CHH had more advanced bone age and were older, taller and heavier than the CDGP boys, yet they had lower trabecular BMD in distal radius (147.7 mg/mm 3 [95% CI, 128–168 mg/mm 3 ] vs. 181.2 mg/mm 3 [172–192 mg/mm 3 ], p  = .002) and distal tibia (167.6 mg/mm 3 [145–190 mg/mm 3 ] vs. 207.2 mg/mm 3 [187–227 mg/mm 3 ], p  = .012), respectively. CHH males had lower cortical thickness at diaphyseal tibia than the participants with CDGP ( p  = .001). These between‐group differences remained significant in corresponding Z ‐scores adjusted for bone age and height ( p  = .001). In CDGP group, serum testosterone correlated positively with trabecular BMD ( r  = 0.51, p  = .013) at distal radius, and estradiol levels correlated positively with trabecular BMD at the distal site of tibia ( r  = 0.58, p  = .004). Conclusions: Five treatment‐naïve male patients with CHH exhibited poorer trabecular BMD than untreated males with CDGP. We speculate that timely low‐dose sex steroid replacement in CHH males may benefit skeletal health in adulthood.